Aerobic capacity and muscle proteome: Insights from a mouse model - Abel Plaza‐Florido; Alejandro Santos‐Lozano; Susana López‐Ortiz; Beatriz G. Gálvez; Joaquín Arenas; Miguel A. Martín; Pedro L. Valenzuela; Tomàs Pinós; Alejandro Lucia; Carmen Fiuza‐Luces (Experimental Physiology)
Abstract We explored the association between aerobic capacity (AC) and the skeletal muscle proteome of McArdle (n = 10) and wild‐type (n = 8) mice, as models of intrinsically ‘low’ and ‘normal’ AC, respectively. AC was determined as total distance achieved in treadmill running until exhaustion. The quadriceps muscle proteome was studied using liquid chromatography with tandem mass spectrometry, with the Search Tool for the Retrieval of Interacting Genes/Proteins database used to generate protein–protein interaction (PPI) networks and enrichment analyses. AC was significantly associated (P‐values ranging from 0.0002 to 0.049) with 73 (McArdle) and 61 (wild‐type) proteins (r‐values from −0.90 to 0.94). These proteins were connected in PPI networks that enriched biological processes involved in skeletal muscle structure/function in both groups (false discovery rate <0.05). In McArdle mice, the proteins associated with AC were involved in skeletal muscle fibre differentiation/development, lipid oxidation, mitochondrial function and calcium homeostasis, whereas in wild‐type animals AC‐associated proteins were related to cytoskeleton structure (intermediate filaments), cell cycle regulation and endocytic trafficking. Two proteins (WEE2, THYG) were associated with AC (negatively and positively, respectively) in both groups. Only 14 of the 132 proteins (∼11%) associated with AC in McArdle or wild‐type mice were also associated with those previously reported to be modified by aerobic training in these mice, providing preliminary evidence for a large divergence in the muscle proteome signature linked to aerobic training or AC, irrespective of AC (intrinsically low or normal) levels. Our findings might help to gain insight into the molecular mechanisms underlying AC at the muscle tissue level.